2014
DOI: 10.1103/physreva.90.023855
|View full text |Cite
|
Sign up to set email alerts
|

Genetic optimization of attosecond-pulse generation in light-field synthesizers

Abstract: We demonstrate control over attosecond-pulse generation and shaping by numerically optimizing the synthesis of few-cycle to subcycle driver wave forms. The optical wave-form synthesis takes place in an ultrabroad spectral band covering the ultraviolet-infrared domain. These optimized driver waves are used for ultrashort singleand double-attosecond-pulse production (with tunable separation), revealing the potentials of the light wave synthesizer device demonstrated by A. Wirth et al. [Science 334, 195 (2011)]. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 48 publications
0
26
0
1
Order By: Relevance
“…The use of a sub-cycle optical waveform as a driving pulse for HHG would enable to naturally limit emission/recollision to a single event, greatly increasing the efficiency of IAP generation, as already demonstrated in first experiments [5], [6]. Additionally, a sub-cycle optical waveform would permit control of the tunnel ionization step [8] and enable to precisely manipulate the electron trajectory in the continuum, optimizing its kinetic energy and the corresponding energy cutoff of the HHG spectrum, realizing experimentally the theoretically predicted "perfect waveform" for HHG [9]- [14].…”
Section: Introductionmentioning
confidence: 85%
“…The use of a sub-cycle optical waveform as a driving pulse for HHG would enable to naturally limit emission/recollision to a single event, greatly increasing the efficiency of IAP generation, as already demonstrated in first experiments [5], [6]. Additionally, a sub-cycle optical waveform would permit control of the tunnel ionization step [8] and enable to precisely manipulate the electron trajectory in the continuum, optimizing its kinetic energy and the corresponding energy cutoff of the HHG spectrum, realizing experimentally the theoretically predicted "perfect waveform" for HHG [9]- [14].…”
Section: Introductionmentioning
confidence: 85%
“…The results to be presented here focus on the possibilities to increase the HHG cutoff, isolate single attosecond pulses from a pulse train while also minimizing its duration, increase harmonic yield at high photon energies, and in general to understand macroscopic processes in HHG. These are based on our theoretical papers about THz assisted attosecond pulse generation [2,3,4], quasi-phase matching of HOH radiation and its study for the special case of perpendicularly propagating IR and THz fields [5,6,7], optimization of attosecond pulse generation in light-field synthesizers [10], and an experimental study of attosecond GD dependence on generation gas pressure [8].…”
Section: Resultsmentioning
confidence: 99%
“…Thus the phase difference between the propagated and generated fields (ϕ q (z) − φ q (z)) is exactly half the value of the phase-difference between ϕ q (0) and ϕ q (z) (see Figure II.11.a). Due to this, the intensity of the radiation increases until z = π/∆k 10 Later it will be shown that this is equivalent to describing the process in a different coordinate frame, and does not affect the results discussed here.…”
Section: Ii42 One-dimensional Descriptionmentioning
confidence: 90%
See 2 more Smart Citations